(untitled) (REMUNOM, 2026)
Motor competence (MC) can be defined as the level of skilled performance in different motor tasks. However, the influence of variables related to body composition and anthropometric measures has not yet been fully clarified. Therefore, the aim of this study was to evaluate the association between MC and sociodemographic, biological, and physical activity factors in children. This cross-sectional study was conducted with 172 children of both sexes, aged 6 to 10 years, from a municipal school. Motor competence was assessed using the Körperkoordinationstest für Kinder (KTK). Height, weight, waist circumference, leg length, foot length, and wingspan were measured. Body Mass Index (BMI) and waist-to-height ratio (WHtR) were calculated. Body composition was assessed by bioelectrical impedance analysis, providing body fat percentage, fat mass, and muscle mass. Bivariate and multivariate analyses were performed using Multiple Correspondence Analysis (MCA) and Multiple Linear Regression, with a significance level of 5%. The mean MC score was 42.66 (± 10.97) points. Significant associations were observed with age, body fat percentage, WHtR, leg length, wingspan, and participation in extracurricular physical activity. MCA indicated a moderate association between higher MC, older age, adequate body fat percentage, and physical activity practice. Multiple regression analysis demonstrated positive associations of MC with age, BMI, and wingspan, and negative associations with body fat percentage and waist circumference. It is concluded that motor competence shows independent associations with biological factors, especially age, wingspan, and body composition indicators. These findings reinforce the need for multifactorial approaches in the assessment and intervention of motor competence in children, considering sociodemographic, biological, and behavioral aspects.